Obscured hemorrhagic pancreatitis after orthotopic heart transplantation complicated with acute right heart failure and hepatic dysfunction: a case report. Issue 1 (December 2016) - Lin, Ting-Wei; Tsai, Meng-Ta; Roan, Jun-Neng; Liu, Yi-Sheng; Tsai, Hong-Ming; Luo, Chwan-Yau
Abstract Background Pancreatitis is a serious complication after cardiac surgery and can lead to significant morbidities and mortality. The incidence of pancreatitis is even higher in patients undergoing heart transplantation than in those undergoing other cardiac surgeries. Nevertheless, the clinical presentations of pancreatitis are frequently atypical in these patients. Case presentation We report a heart recipient who was complicated with acute right heart failure initially after orthotopic heart transplantation and developed devastating unanticipated hemorrhagic pancreatitis 1 month after the transplantation. This crypto-symptomatic pancreatitis was not diagnosed until massive internal bleeding and hemorrhagic shock occurred, because the typical presentations of acute pancreatitis were masked by the intra-abdominal manifestations caused by right heart failure and congestive liver dysfunction. The patient underwent a successful transarterial embolization. Conclusions The causes of pancreatitis after heart transplantation include low cardiac output, immunosuppressant use and cytomegalovirus infection. The typical symptoms of pancreatitis might be not apparent in patients after heart transplantation because of their immunosuppressive status. Furthermore, in patients complicated with right heart failure after transplantation, the manifestation of pancreatitis could be even more obscure. The prompt diagnosis is highly depended on the clinician's astuteness.